Novel antigen-presenting cell imparts Treg-dependent tolerance to gut microbiota - Akagbosu, Blossom; Tayyebi, Zakieh; Shibu, Gayathri; Iza, Yoselin A. Paucar; Deep, Deeksha; Parisotto, Yollanda Franco; Fisher, Logan; Pasolli, H. Amalia; Thevin, Valentin; Elmentaite, Rasa; Knott, Maximilian; Hemmers, Saskia; et al. (Nature, 2022)
Establishing and maintaining tolerance to self-antigens or innocuous foreign antigens is vital for the preservation of organismal health. Within the thymus, medullary thymic epithelial cells (mTECs) expressing autoimmune regulator (AIRE) have a critical role in self-tolerance through deletion of autoreactive T cells and promotion of thymic regulatory T (Treg) cell development1–4. Within weeks of birth, a separate wave of Treg cell differentiation occurs in the periphery upon exposure to antigens derived from the diet and commensal microbiota5–8, yet the cell types responsible for the generation of peripheral Treg (pTreg) cells have not been identified. Here we describe the identification of a class of RORγt+ antigen-presenting cells called Thetis cells, with transcriptional features of both mTECs and dendritic cells, comprising four major sub-groups (TC I–TC IV). We uncover a developmental wave of Thetis cells within intestinal lymph nodes during a critical window in early life, coinciding with the wave of pTreg cell differentiation. Whereas TC I and TC III expressed the signature mTEC nuclear factor AIRE, TC IV lacked AIRE expression and was enriched for molecules required for pTreg generation, including the TGF-β-activating integrin αvβ8. Loss of either major histocompatibility complex class II (MHCII) or ITGB8 by Thetis cells led to a profound impairment in intestinal pTreg differentiation, with ensuing colitis. By contrast, MHCII expression by RORγt+ group 3 innate lymphoid cells (ILC3) and classical dendritic cells was neither sufficient nor required for pTreg generation, further implicating TC IV as the tolerogenic RORγt+ antigen-presenting cell with an essential function in early life. Our studies reveal parallel pathways for the establishment of tolerance to self and foreign antigens in the thymus and periphery, respectively, marked by the involvement of shared cellular and transcriptional programmes.
CRIS-Team Scopus Importer:2023-03-23